Introdução à criptografia e atividades para a Educaão Básica - Deparis, Dafne de Moraes (2021)
The objective of the work was to study aspects of Cryptography, such as its meaning, history and cryptographic methods, especially RSA Cryptography, including definitions, theorems, propositions and examples about integer arithmetic, that is, the mathematics involved in the functioning of RSA Cryptography. Finally, we made some suggestions to activities with application in Elementary and High School, involving cryptography.